Investigating the Role of Interferon Regulatory Factor 3 in Response to Genotoxic Stress - Davidson, Adam (Université d'Ottawa / University of Ottawa, 2013)
Interferon regulatory factor 3 (IRF3) plays an important role in activating the innate immune response in a variety of conditions, including viral infection. As well as regulating the immune response to viruses, IRF3 is involved in regulating cellular functions including apoptosis. Apoptosis and the inflammatory response to viral infection are very different; therefore, it is obvious that IRF3 plays dramatically different roles in the cell depending on the conditions. We previously identified a non-activating phosphorylation of IRF3 in response to adenovirus (Ad) in which Serine-173 is phosphorylated. In addition to Ad infection, IRF3- S173 is phosphorylated in response to genotoxic stresses including ultraviolet (UV) irradiation and etoposide. In this study, I show that this phosphorylation event is involved in a variety of processes including protein stability, cell survival and IRF3 regulation. Thus, phosphorylation of IRF3-S173 is a novel and important event in a complex regulatory pathway of an integral protein.
Keywords: Interferon; Interferon Regulatory Factor 3; Genotoxic Stress; Adenovirus; DNA Damage